LITERATURE REVIEW : THE INFLUENCE OF FINANCIAL TECHONOLOGY, FINANCIAL LITERACY, INVESTMENT MOTIVATION AND RISK PERCEPTION ON INVESTMENT INTEREST IN GENERATION Z IN TAMBUN SELATAN DISTRICT - Salsabila Aninda Putri; Adi Wibowo Noor Fikri; Christophorus Indra Wahyu Putra (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This research aims to analyze the influence of financial technology, financial literacy, investment motivation, and risk perception on investment interest in generation Z in Tambun Selatan District. This research was conducted using the questionnaire distribution method as a data collection tool. The population in this study is generation Z in Tambun Selatan District with a research sample consisted of 80 respondents. The data analysis technique in this research uses Partial Least Square (PLS).